2013
DOI: 10.1016/j.msea.2013.04.108
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of magnesium alloy with high strength and heat-resistance by hot extrusion and ageing

Abstract: A Mg-11Gd-4.5Y-1.5Zn-1Nd-0.5Zr alloy with high-strength and heat-resistance has successfully been prepared by hot extrusion and subsequent ageing. It exhibits an ultimate tensile strength of 473 MPa, 0.2% proof stress of 373 MPa and elongation to failure of 4.1% at room temperature. At 250 °C, this alloy shows an ultimate tensile strength of 369 MPa, 0.2% proof stress of 316 MPa and elongation to failure of 6.3%. Its good mechanical properties and thermal stability are attributed to the dispersion of large vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Based on EBSD results, AEZ830 has a weaker initial texture intensity (6.435) than AZ80 (7.702) after hot extrusion, which further confirmed that the addition of rare earth elements can lead to comparably weaker textures during deformation processing and/or subsequent annealing than conventional Mg alloys [5,6,28,29]. This phenomenon could be attributed to the hypothesis that the solute (Y,Gd) suppressed basal slip by the solid solution strengthening mechanism and promoted prismatic crossslip via a solute softening mechanism, which would promote nonbasal slip and induce a weakened basal texture during deformation processes [29].…”
Section: Crystallographic Texturementioning
confidence: 65%
See 1 more Smart Citation
“…Based on EBSD results, AEZ830 has a weaker initial texture intensity (6.435) than AZ80 (7.702) after hot extrusion, which further confirmed that the addition of rare earth elements can lead to comparably weaker textures during deformation processing and/or subsequent annealing than conventional Mg alloys [5,6,28,29]. This phenomenon could be attributed to the hypothesis that the solute (Y,Gd) suppressed basal slip by the solid solution strengthening mechanism and promoted prismatic crossslip via a solute softening mechanism, which would promote nonbasal slip and induce a weakened basal texture during deformation processes [29].…”
Section: Crystallographic Texturementioning
confidence: 65%
“…It is well known that the magnesium components fabricated by mechanical forming, such as hot extrusion, usually exhibit higher strength and ductility than as-cast ones. Thus, many magnesium alloy systems were fabricated by mechanical forming [3][4][5][6]. One notable example is the extruded AZ80 (Mg-8Al-0.5Zn, wt%) alloy, which has high strength, good ductility, and low cost [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…The Mg 5 RE phase particles were located at grain boundaries so that they served as reinforcement of the grain boundaries by particle pinning. Yu et al [11] suggested that the Mg 5 RE particles had a good thermal stability so that a large number of them remained in the alloy after long-term annealing at 450 °C. As shown in Fig.…”
Section: Compressive Behaviors and Characteristicsmentioning
confidence: 99%
“…It was reported that the addition of Y and Gd in Mg alloys was able to increase the tensile strengthen and creep resistance significantly via age hardening and solid solution strengthening [6][7][8][9]. The obtained thermally stable β-Mg 24 Y 5 and β-Mg 5 Gd phases, which could effectively pin the motion of grain boundaries, are seen to improve the hightemperature performance of Mg alloys [10,11]. Zn addition to Mg-RE alloys leads to the formation of long-period stacking ordered (LPSO) phase, which plays an important role in producing high strength Mg alloys with good ductility [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation